The most compact scission configuration of fragments from low energy fission of U-234 and U-236 - Montoya, Modesto (2010)
Using a time of flight technique, the maximal values of kinetic energy as a function of primary mass of fragments from low energy fission of U-234 and U-236 were measured by Signarbieux et al. From calculations of scission configurations, it is concluded that, for those two fissioning systems, the maximal value of total kinetic energy corresponding to fragmentations (42Mo62, 50Sn80) and (42Mo64, 50Sn80) respectively, are equal to the available energies, and their scission configurations are composed by a spherical heavy fragment and a prolate light fragment, both in their ground state.